KEUNGGULAN BERSAING RIAU POS DALAM PERSPEKTIF RESOURCES-BASED VIEW (RBV) - Tanjung Nuraisyah; Ningsih Suryati Dewita; Fitri Kurniawaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
The purpose of this study was to determine the competitive advantages of RiauPos, and find out the factors that become the strengths, weaknesses, opportunitiesand threats that Riau Pos has. Respondents in this study are representativeparties in providing information related to this research. The results of this studyindicate that: 1) Riau Pos is in quadrant I, namely aggressive growth byimplementing market development strategies, market penetration and productdevelopment. 2) Based on the identification results of the internal environment,Riau Pos has several internal strengths including: reputation, owning localeditions and the position of Riau Pos which is under the conglomerate group. 3)The results of research on external identification, Riau Pos has opportunities inthe form of political conditions that are still stable, demand for advertisements isstill large, and support from the community and government. After the researcherstudied the situation that occurred in the company, the researcher noticed thatchanges in the external environment could not be prevented, especially inadvances in digital technology, so companies needed to anticipate by changingmarket strategies, and taking advantage of technological changes and utilizinghuman resources as efficiently as possible. Keywords : competitive advantage, resources-based view, SWOT analysis